Bolsa família, escolha ocupacional e informalidade no Brasil - Ana Luiza Neves de Holanda Barbosa; Carlos Henrique L. Corseuil (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This study analyzes the impact of conditional cash transfer program Bolsa Familia in the occupational composition Brazilian labor market. The methodology relies on a discontinuity in the program elegibility rule regarding children's age to attain the identification of a LATE parameter. The analysis is carried out with 2006 microdata from National Household Sample Survey (PNAD/IBGE). Our results suggest the cash transfer program does not affect the occupational choice of Brazilian adults among formal and informal jobs.
Keywords: I38; O17; 330; income transfer; informal labor; regression discontinuity design